The origin, expansion, and demise of plant species - Levin, Donald A. (Oxford series in ecology and evolution., 2000)
Each plant species has its own unique passage that is affected by a variety of aspects to which it is exposed. This book explores plant species as dynamic entities within this passage, following the four stages of plant-species life that normally occur.